Impaired Recognition of Emotional Faces after Stroke Involving Right Amygdala or Insula - Tippett, Donna C.; Godin, Brittany R.; Oishi, Kumiko; Oishi, Kenichi; Davis, Cameron; Gomez, Yessenia; Trupe, Lydia A.; Kim, Eun Hye; Hillis, Argye E. (Seminars in Speech and Language, 2018)
Despite its basic and translational importance, the neural circuitry supporting the perception of emotional faces remains incompletely understood. Functional imaging studies and chronic lesion studies indicate distinct roles of the amygdala and insula in recognition of fear and disgust in facial expressions, whereas intracranial encephalography studies, which are not encumbered by variations in human anatomy, indicate a somewhat different role of these structures. In this article, we leveraged lesion-mapping techniques in individuals with acute right hemisphere stroke to investigate lesions associated with impaired recognition of prototypic emotional faces before significant neural reorganization can occur during recovery from stroke. Right hemisphere stroke patients were significantly less accurate than controls on a test of emotional facial recognition for both positive and negative emotions. Patients with right amygdala or anterior insula lesions had significantly lower scores than other right hemisphere stroke patients on recognition of angry and happy faces. Lesion volume within several regions, including the right amygdala and anterior insula, each independently contributed to the error rate in recognition of individual emotions. Results provide additional support for a necessary role of the right amygdala and anterior insula within a network of regions underlying recognition of facial expressions, particularly those that have biological importance or motivational relevance and have implications for clinical practice.
Keywords: Emotion perception; facial recognition; stroke; magnetic resonance imaging; brain mapping